Paw Paw Tree, Trinidad - 5 - (:unkn) unknown (Photogelatine Engraving Co. Limited, 2009)
A picture of a bunch of Paw-paw (papaya) at the top of a tree. The fruit is ripe when it feels soft and its skin has attained an amber to orange hue. Affixed to the back of the postcard is a Trinidad and Tobago 12 cents stamp. Postcard number 5.
Colour: Black and White; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Fruit trees--Trinidad and Tobago; Trees--Paw-paw; Carica--Trinidad and Tobago; Papaya--Trinidad and Tobago; 1941